Can Abies alba Needles Be Used as Bio-passive Samplers to Assess Air Quality? - Agnieszka Stojanowska; Maciej Górka; Anita Urszula Lewandowska; Kinga Wiśniewska; Magdalena Modelska; David Widory (Aerosol and Air Quality Research)
Abstract Bio-passive samplers have proved to be good alternate to assess air quality in regions where the use of active samplers is not technically feasible. Here, we tested the potential for Abies alba (silver fir) needles to be used as reliable bio-passive samplers. As these evergreen coniferous trees do not lose their needles in winter these are representative of a full year period. Needle samples were collected in 2013 from 20 different locations within the Holy Cross National Park (Świetokrzyski Park Narodowy, Holy Cross Voivodship, Poland). Both needles and the aerosols deposited on their surfaces were analyzed for their δ13C. Additionally, total carbon (TC), elemental carbon (EC) and organic carbon (OC) were determined only in surface-impacted aerosols using thermo-optical method. The overall objective of our study was to evaluate the possibility to distinguish bio-organic aerosols (crushed needles) from anthropogenically derived aerosols. The highest aerosol mass concentration (4.6 ± 2.4 mg g−1) was observed in samples with the longest exposure time, while the shortest exposure times yielded the lowest ones (1.7 ± 0.7 mg g−1). Aerosols that were enriched in 13C, indicating the impact of human activities, were located close to inhabited areas, at highly elevated points and in places situated outside the park. Our results also prove that one-year-old needles are the most reliable isotope bioindicators. We ultimately recommend that Abies alba needles can be used in future air quality monitoring programs, especially since this method is low cost and easy to implement.